2019
DOI: 10.1186/s12889-019-6972-1
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among school teachers: quantitative and qualitative results from a follow-up study in southern Sweden

Abstract: Background Teachers are at high risk of stress-related disorders. This longitudinal study aimed to (a) identify which occupational, sociodemographic and life-style factors and self-efficacy at baseline that were of importance for burnout, (b) explore associations between changes in the studied factors versus changes in burnout, and (c) by interviews increase the understanding of perceived job demands among teachers. Methods A cohort of 310 Swedish teachers in school-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 33 publications
(44 reference statements)
5
66
0
3
Order By: Relevance
“…The assistant nurses reported the highest scores in physical activity and lifting at baseline [13] and the teachers reported the highest scores in most of the psychosocial dimensions [13]. The teachers may bene t from actions that reduce the demands placed on them, for example, improved organisation and fewer administrative tasks [16]. Measures to reduce the time pressure may be bene cial in all the occupational categories investigated in this study.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 79%
See 1 more Smart Citation
“…The assistant nurses reported the highest scores in physical activity and lifting at baseline [13] and the teachers reported the highest scores in most of the psychosocial dimensions [13]. The teachers may bene t from actions that reduce the demands placed on them, for example, improved organisation and fewer administrative tasks [16]. Measures to reduce the time pressure may be bene cial in all the occupational categories investigated in this study.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 79%
“…The work tasks of the sonographers is, to a high degree, characterized by prolonged sitting in constrained postures [15], while the physical workload among the teachers is varied, and physically relatively light. While time constraints and adverse psychosocial working conditions may be experienced by all ve occupational groups, mental strain is particularly high among teachers [13,16,17]. Hence, the present study population consists of females in common professions in the public sector, with a broad variety of occupational exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Many teachers have been reported to have a high degree of stress and burnout (Manju, 2018;Arvidsson et al, 2019), but some may find satisfaction in working with children, variation and unpredictability, cooperation and teamwork, and autonomy, as discovered by Skaalvik and Skaalvik (2015). The teacher respondents in their study were happy to see children learn, and found contentment in helping them with school learning.…”
Section: Literature Reviewmentioning
confidence: 81%
“…In contrast, the physical workload among the teachers is varied and physically relatively light. While time-pressure and adverse psychosocial working conditions may be present in all of the five occupational groups, the mental strain is particularly high among the teachers [19,30,31]. Hence, these occupational groups were exposed to working conditions that previously have been recognized as risk factors for musculoskeletal pain, concerning ergonomic- [4,32,33] and psychosocial factors [8][9].…”
Section: The Results In Relation To Other Studiesmentioning
confidence: 99%